Análise de aspectos ergonômicos em atividades home office - Melo, Carmem Julianne Beserra (2024)
Telecommuting, commonly known as home office, entails conducting work within one's residential premises. In the realm of ergonomics, existing literature reveals a prevalent lack of adequate guidance for professionals regarding the structuring of their work environments. Within the context of remote domestic workplaces, numerous factors necessitate thorough examination to ensure the health, comfort, and well-being of individuals engaged in such endeavors. The primary aim of this study is to undertake an analysis of ergonomic peculiarities within remote domestic workplaces situated in high-temperature urban areas, specifically within vertical buildings in João Pessoa, Paraíba, Brazil. Initially, a Systematic Literature Review (SLR) was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Subsequently, measurements were taken for lighting levels as per NHO 11:2018 and NBR 8995-1:2013 standards, air temperature following ISO 7730/2005 guidelines, and levels of extremely low frequency non-ionizing radiation (60Hz. A total of approximately 12 remote domestic workstations were examined, with measurements conducted over three consecutive days, spanning 6 to 8 hours of work per day. The professionals' perceptions were evaluated utilizing the Ergonomics Risk Assessment Method (ERAM) research instrument. Multivariate analysis was then employed to scrutinize similarities among perceptual variables. The findings obtained from the SLR were categorized into ergonomic risks, occupational diseases, and management-related aspects. Illumination measurements yielded average values ranging from 27.85 lux with a standard deviation (S) of 17.86 to 259 lux with S = 171.92. Air temperature fluctuated between 25.7°C with S = 2.4 and 31°C with S = 0.52. Non-ionizing radiation levels ranged from 0.09μT with S = 0.028 to 1.16μT with S = 0.085, both exceeding the threshold of 0.04μT, thereby posing a health risk. Principal Component Analysis (PCA) indicated a correlation between discomfort induced by brightness and shoulder discomfort, while ocular and cognitive aspects were associated with occupational ailments. Muscle complaints exhibited multifactorial associations, while concentration levels, social isolation, and professional advancement were also identified as pertinent factors. These PCA outcomes elucidate over 80% of the variability in the original variables and align with the analysis of similarities through cluster statistical testing. The analysis of the aforementioned measurements underscores that remote domestic workstations deviate from established regulatory standards, warranting further ergonomic investigations focused on cognitive and organizational aspects from a holistic perspective. This research contributes to providing insights into the main ergonomic practices in the home office, including the organization of the workspace and suitable furniture. To this end, two layout proposals are presented, featuring two-dimensional and three-dimensional representations tailored to address functional requisites.